Optimization of Blood Pressure in Adult Hypertensive Patients with Lifestyle Modifications - Hussain, Altaf; Hafeez, Muhammad; Naveed, Muhammad; Shah, Syed Umer; Khan, Mohammad Shahid; Shabir, Muhammad Mehtab (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the impact of lifestyle on the optimization of blood pressure in adult hypertensive patientsStudy Design: Quasi-experimental study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, Aug 2019 to Jan 2020Methodology: The study population comprised of 200 hypertension patients reporting for routine follow-up. Patients were divided into two groups. Group-A (controls) had the patients with the continuation of the routine anti-hypertensive medication. At the same time, Group-B (cases) received lifestyle modifications (salt restriction, quitting smoking and daily step count by using a pedometer) in addition to the routine anti-hypertension medication. Control of blood pressure among the groups was compared three months after the start of the study.Results: Mean age of the patients was 46.50±3.56 years. The mean duration of hypertension in the study participants was 5.12±3.24 years. Optimal blood pressure was achieved in 103(51.5%), while this was not achieved in 97(48.5%). With the help of binary logistic regression analysis, we found a statistically significant difference in achieving optimal blood pressure control among the cases and controls. Gender was also statistically significant in achieving control of blood pressure (pvalue